Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Website Menggunakan Notepad++ Pada Materi Bakteri UntukKelas X SMA - Dian Pradita; Retni S. Budiarti; Harlis Harlis (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2019)
Education becomes the basis for the development and advancement of human life so that it is used as to develop their potential through the learning process. The success of the process in the learning activities also influenced by the teaching materials used. One of the teaching materials that can be used is LKPD. Utilization of LKPD based on the website becomes an attractive choice to be used in learning, wide access range and can overcome the limitations of space and time. The purpose of this research is to develop an LKPD based on the website using Notepad ++ on bacteria material for the tenth grade of senior high school, to find out LKPD base on website qualification, and to know the perceptions of teachers and students for the LKPD based on the website in bacteria material. The type of this research is development research using ADDIE model with stages of analysis, design, development, implementation, and evaluation. A subject of the test was two teachers and 12 students in SMA Negeri 8 Kota Jambi. Data in this research is qualitative data and quantitative data. The result of validation by material expert obtained by the percentage 95,31% with very good category and the result of validation by media expert obtained by percentage 93,75% with a very good category. The percentage on the perception of 2 teachers is 91,67% and 83,33% in the very good category. Percentage on the perception of a student is 89,58% with a very good category. Based on the results of the LKPD based on the website using Notepad ++ in bacteria material included in the category very well and can be used as an alternative teaching material to help learners understand the material of bacteria. Keyword: Bacteria, LKPD, Notepad++, Website